2010
DOI: 10.5194/angeo-28-113-2010
|View full text |Cite
|
Sign up to set email alerts
|

The exchange across the tropical tropopause in overshooting convective cores

Abstract: Abstract. Coordinated measurements of Indian MST radar and radiosonde during the passage of overshooting convective cores in SAFAR pilot campaign (May-November 2008) are utilized to quantify the mass flux across the tropopause and strength of the turbulence in up-and down-draft cores. The distribution of retrieved mass flux is found to be wide, ranging from −0.6 (downward flux) to 0.8 kg m −2 s −1 (upward flux). The net mass flux, is, however, from the troposphere to stratosphere, in spite of the existence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…None of the studies compared the vertical profiles as a function of season, region, and rain type to know why and where (at what height) the variations are large? Most of the above studies have not discussed the regional and seasonal variability of the shallow rain in India and its surroundings. It will be shown later that the shallow rain, indeed, is important and occurs preferentially in some regions of India. None of the above studies quantified the morphological features of virga rain (rain that evaporates before reaching the surface), like its vertical structure and its occurrence in different seasons and types of rain. Although the impact of overshooting convection on stratosphere‐troposphere exchange is known to a great extent through case studies [ Holton et al ., ; Rao et al ., ], several fundamental statistical issues remain. For example, how often the convection penetrates into the upper troposphere (and overshoots the tropopause)?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the studies compared the vertical profiles as a function of season, region, and rain type to know why and where (at what height) the variations are large? Most of the above studies have not discussed the regional and seasonal variability of the shallow rain in India and its surroundings. It will be shown later that the shallow rain, indeed, is important and occurs preferentially in some regions of India. None of the above studies quantified the morphological features of virga rain (rain that evaporates before reaching the surface), like its vertical structure and its occurrence in different seasons and types of rain. Although the impact of overshooting convection on stratosphere‐troposphere exchange is known to a great extent through case studies [ Holton et al ., ; Rao et al ., ], several fundamental statistical issues remain. For example, how often the convection penetrates into the upper troposphere (and overshoots the tropopause)?…”
Section: Introductionmentioning
confidence: 99%
“…6. Although the impact of overshooting convection on stratosphere-troposphere exchange is known to a great extent through case studies [Holton et al, 1995;Rao et al, 2010], several fundamental statistical issues remain. For example, how often the convection penetrates into the upper troposphere (and overshoots the tropopause)?…”
Section: Introductionmentioning
confidence: 99%
“…Occurrence of clear air turbulence in the tropics has been reported in Roach and Bysouth [1]. Severe turbulence in the significant convection over the tropics has been observed in the radar as reported in Rao et al [2]. Ahmad and Proctor [3] studied some convection induced turbulence cases using large eddy simulations and found that there were areas of significant turbulence upwind of the convection in the upper level of the troposphere.…”
Section: Introductionmentioning
confidence: 81%
“…Secondly, this is a way for the regressor to account for the spatial precipitation structure over Switzerland, for example Alpine regions with relatively poor visibility, where precipitation tends to be underestimated by the RZC product are characterized by low radar fractions from the three lower radars (Albis, La Dôle and Monte Lema). Surprisingly the spectral width 10 S w seems to play a relatively large role, which can be due to the fact that it is an indicator of convection (Hooper et al, 2005;Rao et al, 2010), which leads to different relations between precipitation and radar observables. Note also that the relatively low importance of the height (in fact this is the average weighted height of the observations aloft) and the visibility is likely explained by the fact that these variables are already included in the exponential weighting (Section 3.3 and, for the visibility, in the correction of Z h and Z v ( Table 2).…”
Section: Choice Of Input Featuresmentioning
confidence: 99%